Hypertension and hypercholesterolemia: comparison of self-reported information and objective measures from the first Portuguese National Health Examination Survey (INSEF) - Kislaya, Irina (2019)
This study compares self-reported and examination-based prevalence of hypertension and hypercholesterolemia using data from the Portuguese National Health Examination Survey (n=4911), that combines personal interview and clinical measurements. Sensitivity and specificity of self-reported hypertension and hypercholesterolemia were calculated, logistic regression was used to identify factors associated to incorrect self-reports. Self-reports of hypertension and hypercholesterolemia showed high specificity but low sensitivity. Age, education and use of healthcare services were associated to incorrect self-reports of both conditions. Adding objective measurements to self-reported data allow better understanding of socioeconomic inequalities in health.